ELEKTRODEKOLORISASI LIMBAH CAIR ZAT WARNA JINGGA DAN HIJAU DARI INDUSTRI SARUNG TENUN SAMARINDA MENGGUNAKAN ELEKTRODA PbO2/Pb - Yulieta, Afifah Nur; Wirawan, Teguh; Panggabean, Aman Sentosa (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Electrodecolorization of liquid waste from Samarinda Seberang woven sarong industry using PbO2/Pb electrode was to reduce the dye content of Samarinda Seberang woven sarong waste by electrodecolorization method using lead (Pb) as cathode and lead dioxide (PbO2) as anode. Electrodecolorization of Direk orange and green dyes was carried out by varying the working potential, electrolyte concentration, time and dye concentration. The optimum condition of the Direk orange dye solution is using a working potential of 12 volts, 0.2 M Na2SO4 electrolyte concentration for 15 minutes and the Direk green dye solution is at a working potential of 10.5 volts, 0.2 M Na2SO4 electrolyte concentration for 15 minutes. The percentage of decolorization of the waste liquid sample of the Samarinda orange woven sarong industry using the PbO2/Pb electrode at the maximum condition is 99.58% and the percentage of decolorization of the waste liquid sample of the Samarinda green woven sarong industry using the PbO2/Pb electrode at the maximum condition is 98.46%. Keywords: Electrodecolorization, PbO2/Pb electrode, Na2SO4 electrolyte, Samarinda woven sarong industry waste.